Implementación de un sistema domótico de video vigilancia aplicando la metodología mobile d sobre la plataforma android para el control de la seguridad de las salas de docentes de la unidad académica C.I.Y.A – la matriz Universidad Técnica de Cotopaxi en el periodo académico noviembre 2014-agosto 2015 - Chicaiza Angamarca, Doris Karina (2016)
The present thesis has as theme “IMPLEMENTATION OF A HOME AUTOMATION SYSTEM OF VIDEO SURVEILLANCE APPLYING THE METHODOLOGY MOBILE D ON THE PLATFORM ANDROID FOR THE CONTROL OF THE SECURITY OF THE TEACHER’S ROOM OF THE ACADEMIC UNIT DE C.I.Y.A – THE MATRIX TECHNICAL UNIVERSITY COTOPAXI IN THE NOVEMBER 2014-AGUST 2015 ACADEMIC TERM”, and it is addressed to teachers of the academic unit of Sciences of the Engineering and Applied of the Technical University Cotopaxi....